Revegetation of Damaged Forest Slope Used Gabion Wall System Containing Substrates with Wood Meal - Ha, Si-Young; Jung, Ji-Young; Park, Jae-Hyeon; Yang, Jae-Kyung (Journal of Agriculture & Life Science, 2022)
Gabion was unfavorable to the reconstruction of the landscape caused by limit plant growth because of commonly filled with stone. Therefore, gabion was need substrate as possible to plant growth for harmonize with the surroundings and prevent of erosion. The objective of this study was to evaluate the effect of substrates based growing media containing wood meal on physical property (moisture content), chemical properties (organic matter and C/N ratio), plant cover and plant species in gabion. The substrates were composed of soil and soil mixed with growing media (9:1 (v/v) and 4:1 (v/v)). The growing media was prepared by mixing the basic materials, such as peat, perlite, with the specific materials, such as steam treated wood meal (Quercus mongolica) and NH4NO3. Field experiments were carried out on a damaged forest slope, South Korea, from January to November. The results, the moisture content of soil mixed with growing media (4:1, v/v) was maintained high value than others during the thermophilic period and consistently high organic matter which at an advantage for long term plant growth for 11 months. We were confirmed soil mixed with growing media (4:1, v/v) was an advantage to keep C/N ratio for plant growth period. The growing media based substrates has high plant cover percentage and advantage to plant growth for long term. And to conclude, in general the project is a success considering that few repairs or follow up will be necessary. This technique offers a solution to create a better harmony with the surrounding environment.